THE PRINCIPLE OF EQUALITY AND LEGAL CERTAINTY IN MURABAHAH CONTRACTS AND CREDIT AGREEMENTS: A COMPARATIVE STUDY OF THE INDONESIAN AND MALAYSIAN LEGAL SYSTEMS - Rahmad Nauli Siregar (Universitas Nurul Jadid, 2025)
This study compares the principles of equality and legal certainty between murabahah contracts in Islamic banking and credit agreements in conventional banking in Indonesia and Malaysia. Both countries share similar socio-religious backgrounds as Muslim-majority nations but differ in their legal systems: Indonesia adopts the civil law system, while Malaysia applies the common law system. This research employed a normative juridical approach through analysis of legislation, scholarly literature, and judicial practices. The findings reveal that the murabahah contract upholds the principle of partnership, positioning customers and banks on an equal footing in accordance with Sharia principles, whereas conventional credit agreements tend to be hierarchical due to standardized clauses dominated by banks. In the Malaysian context, the diversity of murabahah models—such as Bai‘ al-‘Inah, Bay‘ al-Dayn, and Bay‘ bithaman ajil—reflects legal innovation but also generates fiqh debates concerning elements of riba and the validity of the contracts. These findings indicated that strengthening the principles of equality and legal certainty in Sharia financing contracts is essential for maintaining the legitimacy and sustainability of Islamic economic law in Indonesia and Malaysia.